Performance Assessment of a Novel Multianalyte Methodology for Celiac Disease Biomarker Detection and Evaluation of the Serology-Alone Criteria for Biopsy-Free Diagnosis. - Novis, Camille Leite; Wahl, Edward; Camacho, Eric; Aure, Mary Ann; Mahler, Michael; Nandakumar, Vijayalakshmi (Archives of Pathology & Laboratory Medicine, 2024)
Context.--Serology plays a vital role in celiac disease (CD) diagnosis, and the latest European guidelines advocate for biopsy-free diagnoses in patients with ≥10x the upper limit of normal (ULN) of anti-tissue transglutaminase (tTG) immunoglobulin A (IgA) antibodies. Objective.--To assess performance characteristics of a novel automated particle-based multianalyte technology (Aptiva) for anti-tTG and anti-deamidated gliadin peptide (DGP) antibody detection as compared to the traditional enzyme-linked immunosorbent assay (QUANTA Lite). Performance characteristics of the ≥10x ULN anti-tTG IgA criteria for serologic diagnosis of CD were also evaluated. Design.--Sera samples from 703 patients were tested for anti-tTG IgA, anti-tTG immunoglobulin G (IgG), anti- DGP IgA, and anti-DGP IgG antibodies on both platforms. In total, 127 patients had medical information and were classified as CD-positive (n = 58) and CD-negative (n = 69) based on biopsy results. Clinical performance characteristics were evaluated. Results.--Anti-tTG IgA detection showed equal clinical sensitivity and specificity of 91% sensitivity and 99% specificity on both platforms. Anti-tTG IgG resulted in moderate sensitivity of 69% and 72%, but high specificity of 100% and 94% on Aptiva and QUANTA Lite, respectively. Anti-DGP IgG displayed comparable sensitivity of 90% and 81%, and a specificity of 94% and 99%, on Aptiva and QUANTA Lite, respectively. Anti-DGP IgA demonstrated greater sensitivity on QUANTA Lite (83%) than Aptiva (69%) and similar specificities of 97% and 98% on QUANTA Lite and Aptiva, respectively. At ≥10x ULN levels for anti-tTG IgA, Aptiva displayed a sensitivity of 72% and a specificity of 100%, and QUANTA Lite showed a sensitivity of 69% and a specificity of 100%. Conclusions.--Aptiva is a reliable method to measure CD biomarkers with reduced hands-on necessity and high-throughput capabilities. This study supports the use of a ≥10x ULN anti-tTG IgA biopsy-free approach for serologic diagnosis of CD.